An induced annealing technique for SiPMs neutron radiation damage. (20th December 2021) - Cordelli, M.; Diociaiuti, E.; Ferrari, A.; Miscetti, S.; Müller, S.; Pezzullo, G.; Sarra, I.
Abstract: The use of Silicon Photo-Multipliers (SiPMs) has become popular in the design of High Energy Physics experimental apparatus with a growing interest for their application in detector area where a significant amount of non-ionising dose is delivered. For these devices, the main effect caused by the neutron fluence is a linear increase of the leakage current. In this paper, we present a technique that provides a partial recovery of the neutron damage on SiPMs by means of an Electrical Induced Annealing. Tests were performed, at the temperature of 20°C, on a sample of three SiPM arrays (2×3) of 6 mm 2 cells with 50 μm pixel sizes: two from Hamamatsu and one from SensL. These SiPMs have been exposed to neutrons generated by the Elbe Positron Source facility (Dresden), up to a total fluence of 8 × 10 11 n1 MeV-eq /cm 2 . Our techniques allowed to reduced the leakage current of a factor ranging between 15-20 depending on the overbias used and the SiPM vendor. Because, during the process the SiPM current can reach O(100 mA), the sensors need to be operated in a condition that provides thermal dissipation. Indeed, caution must be used when applying this kind of procedures on the SiPMs, because it may damage permanently the devices themself.